2021
DOI: 10.3390/ijms22041758
|View full text |Cite
|
Sign up to set email alerts
|

Neurosteroids and Neurotrophic Factors: What Is Their Promise as Biomarkers for Major Depression and PTSD?

Abstract: Even though major depressive disorder (MDD) and post-traumatic stress disorder (PTSD) are among the most prevalent and incapacitating mental illnesses in the world, their diagnosis still relies solely on the characterization of subjective symptoms (many of which are shared by multiple disorders) self-reported by patients. Thus, the need for objective measures that aid in the detection of and differentiation between psychiatric disorders becomes urgent. In this paper, we explore the potential of neurosteroids a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 69 publications
1
35
0
Order By: Relevance
“…Our results also suggest that both LINC01119 and BDNF mRNA were interacted by ELAVL1 protein, however, the direct interaction between LINC01119 and BDNF mRNA were not observed, suggesting that ELAVL1 protein may function as a scaffold to form the LINC01119-ELAVL1-BDNF complex. Brain-derived neurotrophic factor (BDNF) is a well-studied growth factor that serves many critical functions within the central nervous system (Almeida et al, 2021). It is a member of a unique family of polypeptide growth factors, neurotrophies, which influence the proliferation, differentiation, survival, and death of neuronal and non-neuronal cells (Cappoli et al, 2020;Su et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Our results also suggest that both LINC01119 and BDNF mRNA were interacted by ELAVL1 protein, however, the direct interaction between LINC01119 and BDNF mRNA were not observed, suggesting that ELAVL1 protein may function as a scaffold to form the LINC01119-ELAVL1-BDNF complex. Brain-derived neurotrophic factor (BDNF) is a well-studied growth factor that serves many critical functions within the central nervous system (Almeida et al, 2021). It is a member of a unique family of polypeptide growth factors, neurotrophies, which influence the proliferation, differentiation, survival, and death of neuronal and non-neuronal cells (Cappoli et al, 2020;Su et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to emphasize that the dysregulation in basal and reactive HPA axis in PTSD is complex and may also involve a variety of steroid compounds, including the neuroactive steroids, such as dehydroepiandrosterone (DHEA), its sulphate ester dehydroepiandrosterone sulphate (DHEA-S), allopregnanolone and pregnanolone. Alterations in the synthesis of neuroactive steroids has been associated with increased PTSD symptoms in humans [ 141 , 142 , 143 ] and in animal studies [ 144 , 145 , 146 , 147 ]. A marked decrease in cerebrospinal (CSF) levels of allopregnanolone and its equipotent stereoisomer, pregnanolone has been found in women with PTSD, and is apparently due to a block in ALLO synthesis at 3α-HSD [ 141 ].…”
Section: Discussionmentioning
confidence: 99%
“…BDNF the neurotrophic factor that controls synaptic plasticity [ 52 , 53 ]. Several studies reported increased BDNF levels following Allopregnanolone administration [ 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%